Entre o leão e as formigas: fronteiras dialéticas do contrabando e do descaminho - Costa, Roberto Rigaud Navega (2021)
In the present work, we seek, initially, from a historical-materialist dialectic perspective, to approach the theme of the institutional fight against the so-called sacoleiro circuit, emphasizing research in the fight against smuggling and embezzlement, relating it to national, state, and municipal public policies of the State in its different spatial scales, more specifically observing the western region of the state of Paraná, in the stretch of territory that comprises the municipality of Foz do Iguaçu in its border articulation with Ciudad del Este, in Paraguay. To this aim, we have tried to describe the definitions of the concept of border, published by relevant researchers of the subject, in bibliographical research that has the purpose of establishing which meaning of this concept we will use in this Master's dissertation. We start from the observation that in the border between Foz do Iguaçu and Ciudad del Este, there is, historically, a direct association with smuggling and embezzlement and that such illegal activities share with the Brazilian State, in its different scales, a dialectic relationship that markedly affects the local territoriality. Thus, we have some research problems to solve: why, despite the enormous structure to fight crime in Foz do Iguaçu and the region, there are no significant results? How is the fight against smuggling and embezzlement carried out in this territory? How does the so called "sacoleiro" circuit work on the part of the "sacoleiros" and "larajas"? We want, then, to make explicit the dialectic relationship between the State and the so-called "sacoleiro" circuit, between the state inspection and border control agencies and the erpetrators of illicit activities in the same border; to find, make explicit, establish, where do we point out the fundamental contradiction that justifies the statement that there is a dialectic relationship between both parties in this scenario of border conflict; to give voice, or visibility, to the speeches of the parties involved in the creation, expansion, and maintenance of the contradiction as the general objective of our case study. We start from the assumption that there is a poorly explained relationship in the area studied by us, where illicit border acts are partially punished, partially tolerated, and we must understand this scenario. To account for the proposed work, we will use a comprehensive theoretical reference, with authors and works that subsidize the research, such as Marx, Politzer, Sartre, Certeau, Cardin, Elias, Geertz, Albuquerque, etc. Our methodology will use a dialectic materialist historical approach, seeking objective reality data from fieldwork, making interviews with representatives of the Military Police-PR, Civil Police PR, Federal Revenue Service of Brazil, Federal Highway Police, Union of Mototaxi drivers of Foz do Iguaçu and region, Union of taxi drivers of CDE (FETACE), Union of vans of CDE (A. T.A.C.A.), Policía Nacional del Paraguay (PNP) and with 21 other sentenced by the Federal Justice in Foz do Iguaçu, who was doing community work in the 14th BPM-PM. We hope that at the end of the dissertation we have contributed to a greater scientific understanding of the problems involving border illegalities in the territory studied, as well as to present a way of using dialectical logic in this type of field research, where we believe it is of great value.